PENGARUH PENGERINGAN TERHADAP DAYA KECAMBAH BUI BEBERAPA JENIS CITRUS. - G. PANGGABEAN; J. HANSON; N. WULUARNI; SOETJIPTO SOETJIPTO (BERITA BIOLOGI, 1987)
G. PANGGABEAN, J. HANSON & N. WULIJARNI - SOETJIPTO 1987. The effect of drying on the viability of Citrus seeds. Berita Biotogi 3(7):330 - 332. The effect tesistence drought on the germination of 4 species of the Citrus seeds were studied under the laboratory conditions.The germination of the C.amblycarpa and C. aurantifolia seeds were still high at the moisture content less than 10 %. Meanwhile, the germination of C. grandis seeds were high at 10 % moisture content but the viability of the seeds were low at the moisture content below 10 %.Various methods of drying were investigated on the C. reticulata seeds. The best germination of the seeds were treated prior drying the seeds under the laboratory conditions. The germination of the seeds decreased rapidly under silica gel, dehumidifier and drying in the oven at 40°C.